تدابير وليم الفاتح في مملكة انكلتراوانعكاساتها على مؤسسات الحكم والادارة فيها 1066—1087 - عبد الكاظم عجه حسنين (Journal of College of Education, 2019)
This Academic Study reviews the achievements of the English King William the Conqueror in establishing the constants of governance and administration in England after its opening in 1066. It deals with an analytical perspective the dimensions of its achievements in these two aspects and their effects. The whole of the English System in all fields, Political and Military, and all the Infrastructure of England, Made the constants of his regime a pillar that none of his predecessors dared ignore, but added much to him, in the same way as William the Conqueror, The true founder of the Kingdom of England Throughout its medieval history, Its accomplishments at various levels with the reasons for its creation, the motivations that led it to retain some of them as before, and to make minor changes to the other, to replace the new systems according to his political vision, Model England was keen to take advantage of the experience and the experience of the political, military and economic systems, and the exclusion of the negative aspects, taking into account the specificity of England, and the circumstances surrounding during the comprehensive change, which was keen to achieve the program, and my study also dealt with the consequences of what he did to England and the system of rule anotheinstitutions.